Taxonomy and systematics of Hyaloscyphaceae and Arachnopezizaceae - Kosonen Timo; Huhtinen Seppo; Hansen Karen (Naturalis Biodiversity Center, 2022)
The circumscription and composition of the Hyaloscyphaceae are controversial and based on poorly sampled or unsupported phylogenies. The generic limits within the hyaloscyphoid fungi are also very poorly understood. To address this issue, a robust five-gene Bayesian phylogeny (LSU, RPB1, RPB2, TEF-1α, mtSSU; 5521 bp) with a focus on the core group of Hyaloscyphaceae and Arachnopezizaceae is presented here, with comparative morphological and histochemical characters. A wide representative sampling of Hyaloscypha supports it as monophyletic and shows H. aureliella (subgenus Eupezizella) to be a strongly supported sister taxon. Reinforced by distinguishing morphological features, Eupezizella is here recognised as a separate genus, comprising E. aureliella, E. britannica, E. roseoguttata and E. nipponica (previously treated in Hyaloscypha). In a sister group to the Hyaloscypha-Eupezizella clade a new genus, Mimicoscypha, is created for three seldom collected and poorly understood species, M. lacrimiformis, M. mimica (nom. nov.) and M. paludosa, previously treated in Phialina, Hyaloscypha and Eriopezia, respectively. The Arachnopezizaceae is polyphyletic, because Arachnoscypha forms a monophyletic group with Polydesmia pruinosa, distant to Arachnopeziza and Eriopezia; in addition, Arachnopeziza variepilosa represents an early diverging lineage in Hyaloscyphaceae s.str. The hyphae originating from the base of the apothecia in Arachnoscypha are considered anchoring hyphae (vs a subiculum) and Arachnoscypha is excluded from Arachnopezizaceae. A new genus, Resinoscypha, is established to accommodate Arachnopeziza variepilosa and A. monoseptata, originally described in Protounguicularia. Mimicoscypha and Resinoscypha are distinguished among hyaloscyphoid fungi by long tapering multiseptate hairs that are not dextrinoid or glassy, in combination with ectal excipulum cells with deep amyloid nodules. Unique to Resinoscypha is cyanophilous resinous content in the hairs concentrated at the apex and septa. Small intensely amyloid nodules in the hairs are furthermore characteristic for Resinoscypha and Eupezizella. To elucidate species limits and diversity in Arachnopeziza, mainly from Northern Europe, we applied genealogical concordance phylogenetic species recognition (GCPSR) using analyses of individual datasets (ITS, LSU, RPB1, RPB2, TEF-1α) and comparative morphology. Eight species were identified as highly supported and reciprocally monophyletic. Four of these are newly discovered species, with two formally described here, viz. A. estonica and A. ptilidiophila. In addition, Belonium sphagnisedum, which completely lacks prominent hairs, is here combined in Arachnopeziza, widening the concept of the genus. Numerous publicly available sequences named A. aurata represent A. delicatula and the confusion between these two species is clarified. An additional four singletons are considered to be distinct species, because they were genetically divergent from their sisters. A highly supported five-gene phylogeny of Arachnopezizaceae identified four major clades in Arachnopeziza, with Eriopezia as a sister group. Two of the clades include species with a strong connection to bryophytes; the third clade includes species growing on bulky woody substrates and with pigmented exudates on the hairs; and the fourth clade species with hyaline exudates growing on both bryophytes and hardwood. A morphological account is given of the composition of Hyaloscyphaceae and Arachnopezizaceae, including new observations on vital and histochemical characters.